(untitled) (Research, Society and Development, 2021)
This study aimed to analyze research on the theme of Inclusive Education in Stricto Sensu Graduate Programs at the IFTM, investigate the provisions on Inclusive Education established in Law Nº. 13.146, of July 6, 2015 and verify in which Graduate programs. Stricto sensu graduation from the IFTM researches are developed on the subject. The methodology involved bibliographic and documentary research in the IFTM Theses and Dissertations Catalog, with the purpose of raising the necessary data to respond to the general objective of the present work. The results obtained showed that most of the researches were developed in the Professional Master’s Degree in Technological Education (PROFEPT), being a work focused on social and professional inclusion; another presented an analysis of the contribution of Information and Communication Technologies (ICT) to learning; a study developed a mobile application to help autistic children in their daily lives and the last selected survey was related to the IFTM’s Center for Assistance to People with Specific Educational Needs (NAPNE). It is concluded that, given the importance of the subject and the small number of studies in the area, it is necessary to encourage further research, as well as the follow-up of work already developed, as socialized experiences configure strategies to achieve the goals of Inclusive education.